Plasma levels of anabolic steroid hormones from capillary blood sampling during the menstrual cycle in track and field athletes - Sippl, J.; Keiler, A. M.; Krumbholz, A.; Büthe, E.; Pilz, M.; Platen, P. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: The menstrual cycle (MC) is characterized by fluctuations of the sex steroids estrogen and progesterone. However, the cyclic fluctuations of anabolic steroid hormones such as testosterone and androstenedione, which are secreted from both ovaries and the adrenal cortex, and the influence of hormonal oral contraception (OC) are largely unknown in elite female athletes. As the phases of MC might influence athletic performance and strength training adaptations1, a deeper understanding of the secretion and metabolism of anabolic sex steroid hormones through the MC is needed. The present study aimed to investigate the plasma levels of these hormones using capillary blood sampling as a new sampling method during MC in elite athletes with and without OC (wOC/noOC). METHODS: 22 elite track and field athletes participated in a longitudinal study of MC monitoring in sports. 12 athletes with normal MC (n=19 cycles) and 5 athletes with OC (n=10 cycles) (26±6 y, 172±5 cm, 68±7 kg) were included in the analysis. In addition to the progesterone measurement, the intravaginal body temperature was measured daily for 24 hours to determine ovulation. Further, athletes collected capillary EDTA blood before training each Monday, Wednesday, and Friday. Plasma steroid hormones were analyzed by LC-MS/MS. Linear mixed models were used to compare testosterone (T) and androstenedione (A) during different phases of MC/noOC (7-phases: menstruation, mid and late follicular phase (FP), ovulation, and early, mid and late luteal phase (LP) and wOC (7-"phases": 28 days/ 7). The average of T and A was used for statistical comparison between noOC and wOC using the Mann-Whitney-U test. RESULTS: In noOC plasma levels of T and A were significantly higher during ovulation compared to menstruation (T: ovulation: 0,44±0.23 ng/ml; menstruation: 0.30±0.12 ng/ml; 95% CI [0.03 0.18], p=0.032; A: ovulation: 1.45±0.65 ng/ml; menstruation: 0.88±0.38 ng/ml; 95% CI [0.22 0.68], p